MOTHER-DAUGHTER RELATIONSHIP IN CHITRA BANERJEE DIVAKARUNI’S BEFORE WE VISIT THE GODDESS - B.V. BIVIDHA; JEBARUBY, Y. VIGILA (International Journal of Psychosocial Rehabilitation, 2020)
Chitra Banerjee Divakaruni is a prolific writer who has written many novels, short stories and poems. She has published many works, among them Before We Visit the Goddess is one of her finest works. The novel also deals with the diasporic issues of immigrant women. Divakaruni’s works are based on women and the problems they face in life. Her works also deal with the lives of Indian immigrants. The novel is about three generational women Sabitri, Bela and Tara. The whole novel revolves around the life of grandmother, mother and daughter. Here the relationship between Bela and Tara is chosen for this study. Divakaruni depicts the life and loneliness of immigrant women and their failure and success throughout the novel.